(untitled) (Ameghiniana, 2013)
ABSTRACT: TRACE FOSSILS ATTRIBUTED TO ATTA (MYRMICIDAE, HYMENOPTEHA) FROM THE MIOCENE OF LA PAMPA PHOVINCE,ARGENTINA.PALAEOZOOGEOGHAPHIC SIGNIFICANCE.- The first record of an ant’s trace fossil referable to Atta is described. The remains (chambers and ducts of nests) occur in palaeopedological horizons in the Epecuén Formation (Huayquerian age, Late Miocene) at Salinas de Hidalgo, Atreucó Department, La Pampa Province. The locality is situated 6° to the south of the known present-day range of the genus Atta . These ants live today in sub tropical environrnents, with two seasons (dry and rainy ). A new ichnogenus and ichnospecies ( Attaichnus kuenzelii) is proposed. A kuenzelii díffers from the nests built by other Attini (except Atta) in its laying and characteristc chamber distribution and its very Iarge nest size.